Branchial bioenergetics dysfunction as a relevant pathophysiological mechanism in freshwater silver catfish (Rhamdia quelen) experimentally infected with Flavobacterium columnare - Baldissera M.D. (2020)
© 2019 Elsevier LtdFlavobacterium columnare, the causative agent of columnaris disease, is a serious bacterial disease responsible for causing devastating mortality rates in several species of freshwater fish, leading to severe economic losses in the aquaculture industry. Notwithstanding the enormous impacts this disease can have, very little is known regarding the interaction between the host and bacterium in terms of the mortality rate of silver catfish (Rhamdia quelen), as well its linkage to gill energetic homeostasis. Therefore, we conducted independent experiments to evaluate the mortality rates caused by F. columnare in silver catfish, as well as whether columnaris disease impairs the enzymes of the phosphoryl transfer network in gills of silver catfish and the pathways involved in this inhibition. Experiment I revealed that clinical signs started to appear 72 h post-infection (hpi), manifesting as lethargy, skin necrosis, fin erosion and gill discoloration. Silver catfish began to die at 96 hpi, and 100% mortality was observed at 120 hpi. Experiment II revealed that creatine kinase (CK, cytosolic and mitochondrial) and pyruvate kinase (PK) activities were inhibited in silver catfish experimentally infected with F. columnare, while no significant difference was observed between experimental and control groups with respect to adenylate kinase activity. Activity of the branchial sodium-potassium pump (Na+, K+-ATPase) was inhibited while reactive oxygen species (ROS) and lipid peroxidation levels were higher in silver catfish experimentally infected with F. columnare than in the control group at 72 hpi. Based on these data, the impairment of CK activity elicited by F. columnare caused a disruption in branchial energetic balance, possibly reducing ATP availability in the gills and provoking impairment of Na+, K +ATPase activity. The inhibition of CK and PK activities appears to be mediated by ROS overproduction and lipid peroxidation, both of which contribute to disease pathogenesis associated with branchial tissue.